2019
DOI: 10.1177/1465116518824022
|View full text |Cite
|
Sign up to set email alerts
|

United in fear: Interest group coalition formation as a weapon of the weak?

Abstract: Although many interest groups work together perpetually, most academic studies agree that coalition formation does not lead to more influence. In this article, we try to explain these puzzling findings. While former research generally tends to frame the decision of forming an interest group coalition as a strength, in this paper, we argue that coalition building should be considered as a ‘weapon of the weak’. Interest groups fearing that they are insufficiently influential, and whose very existence as an organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…On the contrary, sectional groups, are well-endowed with information linked to a particular policy area, enjoy more direct access to policymakers, rely more on direct strategies, but might also consider indirect strategy as a last resort, especially when facing democratic backsliding. Finally, given the weakness of cause groups, it might be expected they will be interested in building and joining networks as a strategy that might strengthen the mission of advocacy (Hanegraaff and Pritoni 2019).…”
Section: Polish Interest Group Representation System and New Political Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, sectional groups, are well-endowed with information linked to a particular policy area, enjoy more direct access to policymakers, rely more on direct strategies, but might also consider indirect strategy as a last resort, especially when facing democratic backsliding. Finally, given the weakness of cause groups, it might be expected they will be interested in building and joining networks as a strategy that might strengthen the mission of advocacy (Hanegraaff and Pritoni 2019).…”
Section: Polish Interest Group Representation System and New Political Contextmentioning
confidence: 99%
“…Therefore, we distinguish between sectional and cause groups, and we analyze their issues areas, funding and types of activities, as well as whether they use direct or indirect strategies to influence public policies, what type of institutions they approach at the national levels, as well as types of policy-relevant information they possess. Finally, we explore whether they coalesce with other organizations assuming that networking might strengthen them and allow them to survive democratic backsliding (Hanegraaff and Pritoni 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These partnerships can be ad hoc or more durable (Gray and Lowery, 1998). Regardless of the type of partnership, studies have shown that public interest groups tend to engage more frequently in these coalitions than other organizations (Klüver, 2013;Hanegraaff and Pritoni, 2019). This strategy allows them to pool resources, broaden their basis of representation, increase the legitimacy of their cause, and increase the chances of the lobbying activity succeeding (Mahoney, 2008).…”
Section: Collaborationmentioning
confidence: 99%
“…Members of specific interest groups (like business organizations) are generally organizations paying membership fees, who want to know that the group is representing their interests towards institutions by providing expertise and policy input. In contrast, members of diffuse groups (such as civil society organizations) generally do not follow the actions of the group as closely; in order to maintain high membership and funding levels, groups must use more public actions to 'prove' that they are active (Kollman, 1998;Dür and Mateo, 2016;Hanegraaff and Pritoni, 2019). It should be noted that both of these explanations are inherently resource-based and lead to similar predictions and findings: civil society groups (with generally lower funding and more diffuse membership) are more likely to use outside strategies, while specific interest groups are more likely to use inside ones.…”
Section: Statementioning
confidence: 99%
“…These factors essentially affect groups' abilities to mobilize resources (both financial and human) and thereby survive in a competitive strategic environment (see e.g. Hanegraaff et al, 2016;Hanegraaff and Pritoni, 2019).…”
Section: Introductionmentioning
confidence: 99%